(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Concrete is a widely used and versatile building material worldwide. Its appealing characteristics, such as elevated resistance to compression and favourable malleability, consistently allure constructors for its cost effective usage as a building material. Rising population and technological progress in the manufacturing industry have resulted in the extensive usage of consumer goods, thereby posing challenges in managing the waste generated, particularly for non-decomposable materials. In this study work parameters chosen as variable was marble and ceramic waste. The compressive and flexural strength were ascertained after 7 days and 28 days. Marble and ceramic waste were utilized to partially replace sand and coarse aggregate at different replacement levels, while maintaining a constant water-cement ratio. The mix design M25 has been designed in accordance with the IS 10262. The compositions were identified as a combination of different proportions of marble and ceramic waste, from 0%, 10%, 20% and 30%, to assess diverse characteristics.